(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2022)
The study of the interaction of phenothiazine dye methylene blue (MB) and phenantridine dye ethidium bromide (EtBr) with synthetic single-stranded (ss)-poly(rA) has been carried out at the ionic strength of the solution 0.1 mol, in wide interval of ligand/phosphate ratio change, by the method of absorption spectroscopy. The binding curves of MB and EtBr with ss-poly(rA) were obtained. MB was shown to interact with this polynucleotide cooperatively, while for EtBr the cooperativity was not revealed. The binding parameters of MB and EtBr with ss-poly(rA) were determined – association constant K and base number n per binding site. It was shown that both ligands bind to ss-poly(rA) at least by two modes, though the affinity of MB to the polynucleotide is higher by an order, than that of EtBr.